Survey of pork products available to consumers - Hollinger, S.; Unruh, John A. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
A survey was conducted to investigate the variety and price per pound of pork products available to consumers. The survey was conducted in the largest store of each of the three leading supermarket chains in Manhattan, KS. The 217.3 pork products per store (642 total) were categorized into fresh pork, smoked/cured pork, sausages, lunch meats, and pastry/pork combinations, which represented 7.4, 13.9, 32.5, 20.4, and 24.4% of the pork products surveyed, respectively. Retail cuts from the loin were the most numerous and highest priced in the fresh pork category. Retail cuts from the ham and belly (bacon) were the most numerous, but cuts from the loin were the highest priced in the smoked/cured pork category. Sausages included more product variety than any other category. Lunch meat, like sausages, varied greatly in percentage of pork as a meat ingredient. They had the greatest variation in price. Ham lunch meat averaged 129% more in price than the bologna and loaf varieties. Pastry/pork combination products had the highest price and constituted the second most numerous category. Pizza was the most numerous subcategory of pastry/pork combinations. Currently, consumers are able to choose from a wide variety of pork products with variations in value (price).
Keywords: Swine; Pork; Retail; Product variety; Price